11α,15α-Dihydroxyandrost-4-ene-3,17-dione - Shen, Yan-Bing (International Union of Crystallography, 2011)
The title compound, C(19)H(26)O(4), was biotransformed from androstenedione. In the crystal, intermolecular O—H⋯O hydrogen bonds link molecules into a corrugated sheet, which lies parallel to the ab plane. Ring A has a slightly distorted half-chair conformation, rings B and C adopt chair conformations, while the cyclopentane ring D adopts a 14α-envelope conformation.